2000
DOI: 10.1002/(sici)1097-461x(2000)78:4<285::aid-qua11>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on opioid receptors and ligands. I. Molecular modeling and QSAR studies on the interaction mechanism of fentanyl analogs binding to ?-opioid receptor

Abstract: Based on our previous result of the three-dimensional model of the µ-opioid receptor, binding conformations of 13 fentanyl analogs and three-dimensional structures for the complexs of these analogs with µ-opioid receptor were constructed employing the molecular modeling method and our binding conformation search program for ligands (BCSPL). Energetic calculation and quantitative structure-activity relationship (QSAR) analysis indicated a good correlation between the calculated binding energies of fentanyl anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In fact, confl icting pharmacophores have been proposed for each ligand class. [24][25][26][27][28][29][30] For the ␦ -selective SNC 80 derivatives, controversy exists over whether the pharmacophoric determinants of SNC 80 (and analogs) are the same as those for the ␦ -selective opiates NTI and SIOM. [57][58][59] For the fentanyls and arylacetamides, different yet important discrepancies exist.…”
Section: Selective Nonopiate Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, confl icting pharmacophores have been proposed for each ligand class. [24][25][26][27][28][29][30] For the ␦ -selective SNC 80 derivatives, controversy exists over whether the pharmacophoric determinants of SNC 80 (and analogs) are the same as those for the ␦ -selective opiates NTI and SIOM. [57][58][59] For the fentanyls and arylacetamides, different yet important discrepancies exist.…”
Section: Selective Nonopiate Ligandsmentioning
confidence: 99%
“…Unfortunately, fentanyl ' s fl exibility makes such methods very diffi cult to interpret. [24][25][26] Potential bioactive conformations have been analyzed, yet the fi ndings have not been conclusive. 30 , 68-70 In particular, the conformation of the phenethyl group has been the topic of numerous discussions.…”
Section: Fentanyl and Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no previous models were observed for such a set of heterogeneous analgesic except the ‘interfamilial’ correlations, to which the data are splitted into families and not treated as a whole. The modeling studies are usually performed on analgesic compounds of small sets that have common structures (7–13). Contrast to what is believed in such cases (that is statistically significant models are obtained only by splitting the data set into different categories), we found that PC‐ANN approach can be applicable to heterogeneous systems such as this study.…”
mentioning
confidence: 99%
“…Despite the importance of fentanyl and the fact that it has been the subject of a large number of structural and conformational studies, [17][18][19][20][21][22][23] the basis of fentanyl binding is still under investigation. 24) According to the Cambridge Crystallographic Database (CSD) 25) the crystal structure of the citrate salt of 1 26) and that of citrate-toluene solvate 27) have been solved.…”
mentioning
confidence: 99%